Fabrication of flexible silver nanowire conductive films and transmittance improvement based on moth-eye nanostructure array. (6th June 2017) - Zhang, Chengpeng; Zhu, Yuwen; Yi, Peiyun; Peng, Linfa; Lai, Xinmin
Abstract: Transparent conductive electrodes (TCEs) are widely used in optoelectronic devices, such as touch screens, liquid-crystal displays and light-emitting diodes. To date, the material of the most commonly used TCEs was indium-tin oxide (ITO), which had several intrinsic drawbacks that limited its applications in the long term, including relatively high material cost and brittleness. Silver nanowire (AgNW), as one of the alternative materials for ITO TCEs, has already gained much attention all over the world. In this paper, we reported a facile method to greatly enhance the transmittance of the AgNW TCEs without reducing the electrical conductivity based on moth-eye nanostructures, and the moth-eye nanostructures were fabricated by using a roll-to-roll ultraviolet nanoimprint lithography process. Besides, the effects of mechanical pressure and bending on the moth-eye nanostructure layer were also investigated. In the research, the optical transmittance of the flexible AgNW TCEs was enhanced from 81.3% to 86.0% by attaching moth-eye nanostructures onto the other side of the flexible polyethylene terephthalate substrate while the electrical conductivity of the AgNW TCEs was not sacrificed. This research can provide a direction for the cost-effective fabrication of moth-eye nanostructures and the transmittance improvement of the flexible transparent electrodes.